Asociación entre manifestaciones de agresividad de perros y mordedura a personas - Curillo T., Mauro (2024)
The aim of the study was to identify the association between dog aggression and bites to people. A survey was conducted using the Dodman and William Campbell methodologies. In total, 400 interviews were conducted with dog owners, randomly sampling four households per block in the city of Abancay, Peru. The study only included crossbred dogs, males and females between 1-4 years old. Results showed that 67.3% (95%CI: 62.5-71.9) of the dogs had ever bitten a person. The causes of aggression associated with bites were when the dog was cornered or chased (OR=6.1; 95% CI: 1.1-33.4; p=0.036), when the dog hides toys and other objects (OR=7.6; 95% CI: 1.6-36.2; p=0.011), when the dog growls if it is eating or resting (OR=6.8; 95% CI: 1.5-30.5; p=0.013) and when the dog stands on two legs on top of the owner (OR=24.9; 95% CI; 5.7-109.3; p=0.000). In conclusion, the manifestations of aggression in dogs associated with bites to people were due to dominance, fear, territoriality and play.